Effects of Industry 4.0 Implementation on Process Management: A Systematic Review of the Literature 2017 – 2024 - PACHECO CARRANZA, ELIZABETH MARIELLA; TORRES VELASQUEZ, JULIO WINSTON; RIVAS MENDOZA, MILAGROS ISABEL (LACCEI, 2025)
The purpose of this study is to evaluate the effects of the implementation of Industry 4.0 in process management in industries in the productive, health and business sectors, as well as to identify the technological tools applied in companies. Therefore, a systematic review of scientific literature was carried out between 2017 and 2024 based on a collection of Scopus data. 22 investigations that met the eligibility criteria were identified. The results show the effectiveness of Industry 4.0 tools when implemented in a company’s processes. These allow for greater versatility in decision-making, the empowerment of processes, and increased quality. The most representative tools are the MES (Manufacturing Execution System), the HORSE system, and the BPM (Good Manufacturing Practices). In conclusion, this study shows the importance of implementing I4.0 to achieve optimal integration of processes in business management, which impacts the performance and productivity of corporations